PENGARUH REPUTASI PERUSAHAAN DAN REPUTASI VENDOR TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL ANTARA - Herwin, Herwin; Abadi, Ferryal (Economic Faculty, Attahiriyah Islamic University, 2018)
This study aims to determine the effect of Corporate Reputation and Vendor Reputation of online purchasing decisions with consumer trust as a variable between. This is triggered from the phenomenon of the number of companies engaged in E-Commerce, but many are still failing. By looking at the big prospects in Indonesia, it is hoped that this research can find out what strategies can be done in order to succeed in E-Commerce. This research uses quantitative research method by conducting survey. Sampling method is purposive sampling. Validity and Reliability Test Results using SPSS v 20.0, and the results of hypothesis using path analysis. Corporate Reputation has a significant effect on Consumer Trust, as well as Vendor Reputation also has a significant effect on Consumer Trust. Then Consumer Trust also affects the Purchase Decision online. Keywords: Reputation, Company, Vendor, Trust, decision, buying